Reboot cinema. (November 2013) - Tryon, Chuck
This article addresses digital three dimensions (3D) by aligning it with the industrial strategy of the reboot. On the one hand, studios seek to create textual novelty by restarting blockbuster franchises through a return to the characters' origins. On the other hand, studios, hardware manufacturers, and theater owners – often led by technological auteurs such as James Cameron and Peter Jackson – have embraced a strategy of technological novelty by seeking to upgrade the moviegoing experience. Both forms of novelty reinforce each other and, in turn, promote what is described as a new form of storytelling that should be understood as a 'reboot cinema.'